1988
DOI: 10.1210/endo-122-1-187
|View full text |Cite
|
Sign up to set email alerts
|

Luteolysis Is Linked to Luteinizing Hormone-Induced Depletion of Adenosine Triphosphatein Vivo*

Abstract: An elevation of ATP levels in luteal cells markedly enhances their response to gonadotropin. In contrast, depletion of ATP in all cells leads to a series of interrelated events that produces irreversible cell injury. Since the corpus luteum has a transient existence, functional regression and involution of this gland play a fundamental role in the regulation of reproduction. The objective of the present studies was to evaluate whether the luteal ATP content may be regulated in an endocrine fashion and whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Luteal cell ATP is rapidly depleted by LH. This appears to be a physiological event as a result of cells undergoing apoptosis (i.e., luteolysis) at the end of the pseudopregnant cycle [382].…”
Section: Female Reproductive Organsmentioning
confidence: 99%
“…Luteal cell ATP is rapidly depleted by LH. This appears to be a physiological event as a result of cells undergoing apoptosis (i.e., luteolysis) at the end of the pseudopregnant cycle [382].…”
Section: Female Reproductive Organsmentioning
confidence: 99%
“…Billig and Rosberg 3 reported that ATP levels in rat granulosa cells are markedly depressed by gonadotropins, and the gonadotropin-induced decrease in ATP can be explained by its increased consumption and/or decreased production. Soodak et al 4 reported that luteinizing hormone depletes luteal ATP levels in luteinized ovaries, and suggested that ovulation causes depletion of luteal ATP levels to ensure irreversible regression and eventual death of the corpora lutea. The findings of a decrease in ATP level during the infusion of gonadotropin are in agreement with the results of some investigators.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that stimulation with follicle stimulating hormone (FSH) or luteinizing hor-mone (LH) depresses the level of ATP in granulosa cells or luteinized ovaries. 3,4 Patwardhan and Lanthier 5 reported that both LH and human chorionic gonadotropin (HCG) induce a rapid increase in ovarian cyclic adenosine 3',5'-monophosphate (cAMP) concentrations. Holmes et al 6 suggested that cAMP is a sufficient signal to initiate the ovulatory process through adenylate cyclase activation.…”
Section: Introductionmentioning
confidence: 99%
“…LH rapidly depletes luteal cell ATP, which appears to be a physiological action, since it occurs during functional luteolysis at the end of the pseudopregnant cycle [501]. The authors suggest that during functional luteolysis, the rising levels of LH that occurs during follicular development and ovulation cause depletion of luteal ATP levels to ensure irreversible regression and eventual death of the corpora lutea of the previous cycle.…”
Section: Ovarymentioning
confidence: 99%